Sequência didática voltada a tópicos de astronomia e astronáutica - Marques, Railson Caxeixa (2023)
This work intends to present and propose a Didactic Sequence focused on topics of Astronomy and Astronautics with an emphasis on Newton's laws, as these sciences when applied in Physics classes, they promote the development of activities significant; The development of the educational product was based on the Theory of Teaching and Learning by David Ausubel and the use of methodological resources such as the history of Physics, workshops, use of stellarium and excel which are fundamental to bring students closer to the topic; The SD application targeted a 1st year high school class at a full-time state school in municipality of Coari, state of Amazonas, and its activities were carried out during the period of the Covid 19 Pandemic with face-to-face classes, where teachers and students were already immunized with one dose of the vaccine; For the study of data collected we use the qualitative and quantitative approach with performance analysis by male and female gender and as a result the final questionnaire consisted of that students have assimilated the proposed concepts, for the teacher SD promotes organization of the teaching and learning process.